A new genus of land planarian (Platyhelminthes, Geoplanidae) for a new 'blind' species. Issue 1 (31st December 2022) - Negrete, Lisandro; Francavilla, Marina Lenguas; Damborenea, Cristina; Brusa, Francisco
Abstract : The morphological and molecular (mitochondrial cytochrome c oxidase subunit I, COI) characterization of a new species of the subfamily Geoplaninae (Geoplanidae) supports the erection of a new genus, Anophthalmoplana gen. nov. The most remarkable feature of Anophthalmoplana horticola sp. nov. is the absence of eyes, a feature so far only recorded in one species of Geoplaninae, Geobia subterranea . Other features of the species are: a narrow, ribbon-shaped body; a gonopore near the posterior tip; a creeping sole almost as wide as body width; cylindrical pharynx; voluminous extrabulbar prostatic vesicle; protrusible penis papilla occupying the whole male atrium; a common ovovitelline duct dorsal to the female atrium; the atrium being lined by an epithelium with a stratified appearance. Based on the mtDNA phylogeny, the specimens studied here form a separate clade from the genus Geobia, thus contradicting its inclusion in this genus or any other of the subfamily Geoplaninae. These results reinforce the morphological differences observed, regarding internal anatomy, from Geobia and other members of Geoplaninae. http://zoobank.org/urn:lsid:zoobank.org:pub:317A4055-BCC8-4B89-A9DC-F96F98E803A5